Trajetória escolar, texto escrito e classe social: um estudo longitudinal - Leiva de Figueiredo Viana Leal (1999)
This work is the result of a longitudinal study carried out at schools that serve students belonging to different socio economic levels.During the priod of eight years the written texts produced by these studentes were collected aiming at analyzing the contidions of the production of written texts at schools and detecting, from the tracing approach the incorporations noticeable in such texts. The theoretical axis utilized in the data analysis adapts two basic concepts: the notion of habitus, as defined in the Sociology of education by Bourdieu and the notion of INTERACTION , as defined in the theories of enunciation defended by BAKHTIN. As far as the scool destinies are concerned, the data analysis shows that the democratic school through its evaluation strategies transforms equal results in differente results, since you can observe that final results have no direct relation with the actual level of competence reched by students. These strategies allow that despite having similar results, only the studentes belonging to higher social levels advance in their schooling process, which can lead to the conclusion that the belong to lower social levels. This inculcation produces the acceptance of fifferences as necessary to the social structure. As one traces the path these students have gone through in the written text teaching learning process it is revealed that the conditions of production of the written text at school are far from a conception of text as possibility of interaction. In this way the school are far from a conception of text as possibility of inteaction.In this way the school allows access to the written text, but does not allow the students to become the actual text producers within a processs of interlocution. The analysis carried out leads to the conclusion that the teaching of writing as it is and has been done constitues the material realization that supports the construction of the habitus.From this was possible to detect in the texts traces and signals (sings) that show the incoporations made by the different subjects and that they are strongly marked by the practices of inculcation in school. It was also possible to notice that these manifestations are not homogenous because they are constituted from the effect of the primary habitus and the secondary habitus, as well as from the way these different subjects (studentes) situate themeselves and perceive their group of belonging. Strong differences being noticed in students belonging to the same social group.